Gas Chromatographic Method: Tool for Rapid and Sensitive Analysis of Residual Solvents in Amoxicillin and Ampicillin Tablets - Sk Manirul Haque; S M Zakir Hossain; Prem Shanker (Chemical Engineering Diponegoro University, 2015)
A simple and sensitive static head space gas chromatographic (SH-GC) method equipped with FID has been developed and validated for simultaneous determination of residual solvents e.g., methanol, dichloromethane and toluene in two therapeutic drugs such as amoxicillin and ampicillin. The separation was achieved with 30 m long Elite - 5 fused silica capillary column and 0.32 mm inner diameter. The developed SH-GC method offered symmetric peak shape, good resolution and reasonable retention time for all the solvents. Beer’s law was obeyed in the concentration ranges 100 – 1200, 50 – 1000 and 50 – 500 ppm for methanol, dichloromethane and toluene, respectively. The method was validated according to international conference on harmonization (ICH) guidelines in terms of specificity, linearity, precision, accuracy, limit of detection, limit of quantitation, robustness and solution stability. The degrees of linearity of the calibration curves, the percent recoveries, relative standard deviation for the method were also determined. All the validation parameters were within the acceptable range. The developed SH-GC method could, therefore, be suitable for simple and rapid detection of trace levels residual solvents in other pharmaceutical products and thereby it could be used for routine analysis in any analytical laboratory.